Complex interplay between β-catenin signalling and Notch effectors in intestinal tumorigenesis. Issue 2 (4th January 2011) - Peignon, Grégory; Durand, Aurélie; Cacheux, Wulfran; Ayrault, Olivier; Terris, Benoît; Laurent-Puig, Pierre; Shroyer, Noah F; Van Seuningen, Isabelle; Honjo, Tasuku; Perret, Christine; Romagnolo, Béatrice
Abstract : Aims: The activation of β-catenin signalling is a key step in intestinal tumorigenesis. Interplay between the β-catenin and Notch pathways during tumorigenesis has been reported, but the mechanisms involved and the role of Notch remain unclear. Methods: Notch status was analysed by studying expression of the Notch effector Hes1 and Notch ligands/receptors in human colorectal cancer (CRC) and mouse models of Apc mutation. A genetic approach was used, deleting the Apc and RBP-J or Atoh1 genes in murine intestine. CRC cell lines were used to analyse the control of Hes1 and Atoh1 by β-catenin signalling. Results: Notch signalling was found to be activated downstream from β-catenin. It was rapidly induced and maintained throughout tumorigenesis. Hes1 induction was mediated by β-catenin and resulted from both the induction of the Notch ligand/receptor and Notch-independent control of the Hes1 promoter by β-catenin. Surprisingly, the strong phenotype of unrestricted proliferation and impaired differentiation induced by acute Apc deletion in the intestine was not rescued by conditional Notch inactivation. Hyperactivation of β-catenin signalling overrode the forced differention induced by Notch inhibition, through the downregulation of Atoh1, a key secretory determinant factor downstream of Notch. This process involves glycogen synthase kinase 3 β (GSK3β) and proteasome-mediated degradation. The restoration of Atoh1 expression in CRC cell lines displaying β-catenin activation was sufficient to increase goblet cell differentiation, whereas genetic ablation of Atoh1 greatly increased tumour formation in Apc mutant mice. Conclusion: Notch signalling is a downstream target of β-catenin hyperactivation in intestinal tumorigenesis. However, its inhibition had no tumour suppressor effect in the context of acute β-catenin activation probably due to the downregulation of Atoh1. This finding calls into question the use of γ-secretase inhibitors for the treatment of CRC and suggests that the restoration of Atoh1 expression in CRC should be considered as a therapeutic approach.